Problems of Learning Planning in The Time of The Covid Pandemic 19 - Syafaruddin, Baso; Ruhaya, Besse; Jamal, Jamal (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This paper discusses learning planning during the COVID-19 pandemic. The purpose of this paper is to provide an overview of the solutions to the problems of learning planning during the COVID-19 pandemic and the ability of educators to formulate learning plans during the COVID-19 pandemic. The study's findings indicate that future learning and planning are crucial. The COVID-19 pandemic requires the ability of an educator to involve parents, pay attention to environmental conditions and the habits of students in their homes. Learning plans that involve parents as supervisors for each student in carrying out learning activities independently Likewise, with the environment and habits of students at home as a form of appreciation for the psychology of the development of students, learning planning can arouse interest and challenge the curiosity of every student towards learning